Frame removal for mushaf Al-Quran using irregular binary region - Bany Melhem, Laith Nazeeh; Arbain, Nur Atikah; Azmi, Mohd Sanusi; Muda, Azah Kamilah; A. Jalil, Intan Ermahani; Ramdan, Jabril (World Academy Of Research In Science And Engineering (WARSE), 2019)
Segmentation is a process to remove frame or frame exists in each page of some releases of mushaf Al-Quran. The fault in segmentation process affects the holiness of Al-Quran. The difficulty to identify the appearance of frame around text areas as well as noisy black stripes has caused the segmentation process to be improperly carried out. In this paper, an algorithm for detecting the frame on Al-Quran page without affecting its content is proposed. Firstly, preprocessing was carried out by using the binarisation method. Then, it was followed with the process of detecting the frame in each page. In this stage, the proposed algorithm was applied by calculating the percentage of black pixel of binary from vertical (column) to horizontal (row). The results, based on experiments on several Al-Quran pages from different Al-Quran styles, demonstrate the effectiveness of the proposed technique